2004
DOI: 10.1111/j.1742-1241.2004.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of perivasculary space under the myocardial bridge in different species

Abstract: Our purpose in this study was to investigate the perivasculary space under the myocardial bridges (MB) in dog, sheep, goat and human hearts. A total of 160 hearts were studied, and perivasculary space under the myocardial bridges was examined under microscope. The specimens belonged to 25 dogs, 100 sheep, 25 goats and 10 humans. Special attention was paid to evaluate the distance between the MB and coronary arteries (CA), CA and underlying myocardium (UM) and to find the relation of concomitant vein number acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(59 reference statements)
0
6
1
Order By: Relevance
“…The present study showed that 47 of 60 hearts had one or more myocardial bridges (78.3%) (Table ), a higher incidence than previously reported by Loukas et al () (34.5%), Ballesteros and Ramirez () (39%), Kosinski and Grzybiak (2001) (41%), Ferreira et al () (55.6%), or Ozbag and Kervancioglu () (70%), but lower than reported by Polacek and Kralove () (85.7%) or Bandyopadhyay et al () (90.4%). The reason why the reported incidences differ is unknown, but interracial differences or the techniques used could provide explanations.…”
Section: Discussioncontrasting
confidence: 41%
“…The present study showed that 47 of 60 hearts had one or more myocardial bridges (78.3%) (Table ), a higher incidence than previously reported by Loukas et al () (34.5%), Ballesteros and Ramirez () (39%), Kosinski and Grzybiak (2001) (41%), Ferreira et al () (55.6%), or Ozbag and Kervancioglu () (70%), but lower than reported by Polacek and Kralove () (85.7%) or Bandyopadhyay et al () (90.4%). The reason why the reported incidences differ is unknown, but interracial differences or the techniques used could provide explanations.…”
Section: Discussioncontrasting
confidence: 41%
“…The MBs are located on the large branches such as ramus interventricularis paraconalis et subsinosus or ramus circumflexux in sheep (Ozbag & Kervancıoglu, 2004). The current study focused on the MB over the ramus interventricularis paraconalis because of its clinical importance (Ferreira et al., 1991; Ishii et al., 2014; Loukas et al., 2006; Möhlenkamp et al., 2002; Teofilovski‐Parapid et al., 2017; Wasilewski et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The MBs are a congenital anomaly (Lee, & Chen, 2015) found in humans and animals (Hadziselimovic et al, 1974;Ozbag, & Kervancıoglu, 2004;Van Nie, & Vincent, 1989). The MBs are absent or rare in horses and pigs, but in goats and sheep, the MBs are seen more often than in humans (Möhlenkamp et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There exist, however, a few descriptions of the issue in reference to human, dog, goat and sheep hearts. In studies by Ozbag and Kervancioglu the distance between the MB tissue and the bridged vessel was measured, as well as between the vessel and the myocardium located below (Ozbag and Kervancioglu 2004). Results obtained referring to the vertical orientation proved to be very accurate and determined the location of the artery in the perivascular space on the basis of one direction.…”
Section: Discussionmentioning
confidence: 99%